Legal Protection of Trademarks for MSME Products in Enhancing Business Competitiveness - Afda'u, Faisal (UNISKA LAW REVIEW, 2024)
The purpose of this research is to identify and analyze Legal Protection of MSME Product Trademarks in Enhancing Business Competitiveness in the Market and to examine and analyze the Legal Dispute Resolution Mechanisms Related to Trademark Infringement of MSME Products, while the method applies a normative legal approach with library research, analyzing trademark protection of MSMEs through legislative and conceptual approaches based on relevant secondary data. The findings show that Law Number 20 of 2016 on Trademarks and Geographical Indications provides strong legal protection to registered trademark owners. Owners are granted exclusive rights for ten years and these rights can be extended under the applicable law. In the event of infringement, owners are authorized to file civil lawsuits through the available legal mechanisms, as regulated under Article 83. Such lawsuits may include compensation claims and requests to stop unauthorized use of the mark. Besides litigation in the Commercial Court, dispute resolution is also possible through alternative means such as mediation and arbitration, in order to accelerate settlement. Criminal aspects of trademark protection are regulated under Article 100, which imposes fines and imprisonment for proven violations. This law enforcement aims to create a deterrent effect and protect entrepreneurs from unlawful actions. Collaboration between the government, trademark owners, and business actors is crucial to encourage effective legal protection, enhance the competitiveness of MSME products, and maintain consumer trust in local products circulating in the market.